Fluxograma de acolhimento das situações de urgência e emergência na atenção primária em saúde - Silveira, Andréia da (Universidade do Vale do Rio dos Sinos, 2020)
Primary Health Care (PHC) is the preferred door of entry into the Unified Health System (SUS), and the Reception with Risk Classification (RRC) is a means of access in the PHC, where qualified listening enables the prioritization of care for patients with acute conditions and chronic conditions in acute state, as it classifies the potential for risk and/or health problems, favoring care in a timely and appropriate manner. Objective: To develop a flowchart for reception of urgency and emergency (UE) situations in the PHC context in the Municipality of Gramado/ RS. Method: This is a methodological research, developed in three stages: descriptive contextualization of the healthcare demands attended in the RRC and the classified as urgency, medications and inputs used for care; documentary research concerning national regulations and policies in UE; development and validation of the reception flowchart for UE in PHC. The study data were collected from the reception of spontaneous demand from January to July 2019, with the prevalent complaints related to the respiratory (21%), musculoskeletal (13%) and gastrointestinal (9%) systems. Through patients` evaluation and risk classification, it was identified that the symptoms related to the cardiovascular system prevailed (31%), followed by intense pain (27%) and fever (10%), as well as the search for assistance for renewing prescriptions and showing exams. It was found that female users predominate, aged between 31 and 40 years. The resolvability of the PHC in relation to attendance due to spontaneous demand was 97%, however 3% were referred to hospital for the continuity of care. The study identified the unavailability of medications to assist UE situations in PHC in the city. For the development of the products of this study, the productions found in the documentary research were used. The flowchart was validated using the Focal Group (FG) technique, in which nurses, doctors and nursing technicians participated. It was found that there is no standardization of care of patients who spontaneously seek health assistance in the municipality's PHC, and that not all nurses perform the RRC. In this sense, the products of this study: development of a reception flowchart for UE situations in PHC, action plan for support and guidelines for the nursing teams and informative folder regarding risk classification, will contribute to the improvement of care in the context of spontaneous demand in Health Units (US).
Keywords: Enfermagem; Atenção primária em saúde; Acolhimento; Classificação de risco; Demanda espontânea; Fluxograma; Nursing; Primary health care; Reception; Risk rating; Spontaneous demand; Flowchart; ACCNPQ::Ciências da Saúde::Enfermagem